Application of Demonstration Method in Writing Text Procedure at SMA Pasundan 1 Cianjur - Windy Sudiastuti (Universitas Suryakanca, 2018)
This article discusses the significance of differences in the ability to write text of complex procedures before and after using the demonstration method and then to observe the interest of student learning in grade XI SMA Pasundan 1 Cianjur. The method used is a quasi-experimental study involving one study group by giving pretest as a preliminary test and postes as a final test to see the difference of learning result then use questionnaire to see interest in learning. Processing results of pretest and postes value, calculated using the help of SPSS application, from wilcoxon test results obtained 0.000 significance meaning less than 0.05 indicates the difference of learning outcomes before and after applied method of demonstration then student learning interest showed good response with 100% answer want to relearn with this method. It was concluded that the application of demosntration method in writing text of complex procedure in class XI of Pasundan 1 Cianjur High School can give significant difference of learning result and student's learning interest showed good attitude.Keywords: demonstration methods, complex text procedures.